Pengaruh Efektivitas Pengelolaan Modal Kerja dan Aktiva Tetap Terhadap Net Profit Margin - Radhi Abdul Halim Rachmat; Ii Halilah (Jurnal Riset Bisnis dan Investasi, 2015)
Working capital and fixed assets is an important component in the internal aspects of a company, with an investment in working capital and fixed assets expected the company is able to obtain the maximum level of profitability. This study aims to determine the extent to which influence effectiveness of working capital and the effectiveness of fixed assets to Net Profit Margin. From the test results simultaneously using the F test, it can be concluded that the effectiveness of the management of working capital and fixed assets Net effect on profit margins. From the results of the partial testing using t test, for the dependent variable is the net profit margin then it can be concluded that the effectiveness of the management of working capital is not partial effect on the profit margin ratio and effectiveness of the management of fixed assets partial effect on the profit margin ratio.